2019
DOI: 10.2176/nmc.oa.2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Infectious Intracranial Aneurysms: Report of Three Cases and Review of the Literature

Abstract: We retrospectively reviewed the cases of three patients with infectious intracranial aneurysms (IIAs), and discuss the indications for surgical and endovascular treatments. We treated two men and one woman with a total of six aneurysms. The mean age was 43.3 years, ranging from 36 to 51 years. One patient presented initially with an intraparenchymal hemorrhage, one with mass effect, and the other one had four aneurysms (one causing subarachnoid hemorrhages and the other causing delayed intraparenchymal hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Growing, symptomatic, or ruptured IIAs are typically treated endovascularly or surgically, with recent studies favoring endovascular treatment. [ 1 ] Chun et al . proposed an algorithm in which endovascular management be pursued in ruptured IIAs in non-eloquent areas without evidence of hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing, symptomatic, or ruptured IIAs are typically treated endovascularly or surgically, with recent studies favoring endovascular treatment. [ 1 ] Chun et al . proposed an algorithm in which endovascular management be pursued in ruptured IIAs in non-eloquent areas without evidence of hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…proposed an algorithm in which endovascular treatment is preferred for management of small, distal IIAs with or without concurrent cardiovascular instability. [ 1 ] In this current case, endovascular treatment was chosen due to the distal location and small vessel size, as well as the patient’s poor clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors comment that if the IIA enlarges, fails to resolve, or ruptures on medical management, the next recommendation is typically for neurosurgical or neuro-endovascular treatment [20]. Regarding surgical intervention, it has been shown that endovascular management is associated with easier access to distal locations, higher success in the treatment of multiple aneurysms and lower hemorrhagic risk compared to microsurgical craniotomies, and can potentially be performed under non-general anesthesia, an important consideration in cardiac patients [20][21][22]. In terms of embolization material, detachable coils or liquid embolization agents such as N-butyl cyanoacrylate, Onyx, or others have been used [21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical intervention, it has been shown that endovascular management is associated with easier access to distal locations, higher success in the treatment of multiple aneurysms and lower hemorrhagic risk compared to microsurgical craniotomies, and can potentially be performed under non-general anesthesia, an important consideration in cardiac patients [20][21][22]. In terms of embolization material, detachable coils or liquid embolization agents such as N-butyl cyanoacrylate, Onyx, or others have been used [21]. The friability of the vessel walls and wide neck structure can make surgical techniques such as clipping difficult [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation